Pengaruh Minat, Disiplin dan Kemampuan Berpikir Kritis terhadap Hasil Belajar di SMK PGRI 2 Sidoarjo (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to analyze the influence of learning interest, learning discipline, and critical thinking skills on student learning outcomes in the Simple Financial Processing subject for class XI MPLB at SMK PGRI 2 Sidoarjo. Learning outcomes are understood as skills or abilities acquired by students after participating in the learning process, the success of which is measured through scores in the form of numbers, symbols, or letters. Three factors selected in this study as independent variables are learning interest, learning discipline, and critical thinking skills. This type of research is quantitative research with an explanatory approach, which aims to explain the cause-and-effect relationship between these variables. The population in this study were all 102 class XI MPLB students. The sampling technique used non-probability sampling with a total sampling type, so that the entire population was sampled. Data collection was carried out by distributing questionnaires to students. The data obtained were then analyzed using SPSS version 27 software. Before conducting multiple linear regression analysis, validity and reliability tests were first conducted to ensure that the instruments used were appropriate and consistent in measuring the variables studied. The analysis results show that the three independent variables—learning interest, learning discipline, and critical thinking skills—have a significant influence on student learning outcomes. Therefore, it can be concluded that improvements in these three aspects will positively impact student learning outcomes in the subjects studied.